Characterization of a single-chain variable fragment recognizing a linear epitope of a?: a biotechnical tool for studies on Alzheimer's disease? - Dornieden, Silke; Mueller-Schiffmann, Andreas; Sticht, Heinrich; Jiang, Nan; Cinar, Yeliz; Woerdehoff, Michael; Korth, Carsten; Funke, Susanne Aileen; Willbold, Dieter (PLoS ONE, 2013)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder with devastating effects. Currently, therapeutic options are limited to symptomatic treatment. For more than a decade, research focused on immunotherapy for the causal treatment of AD. However, clinical trials with active immunization using A? encountered severe complications, for example meningoencephalitis. Consequently, attention focused on passive immunization using antibodies. As an alternative to large immunoglobulins (IgGs), A? binding single-chain variable fragments (scFvs) were used for diagnostic and therapeutic research approaches. scFvs can be expressed in E. coli and may provide improved pharmacokinetic properties like increased blood-brain barrier permeability or reduced side-effects in vivo. In this study, we constructed an scFv from an A? binding IgG, designated IC16, which binds the N-terminal region of A? (A?(1-8)). scFv-IC16 was expressed in E. coli, purified and characterized with respect to its interaction with different A? species and its influence on A? fibril formation. We were able to show that scFv-IC16 strongly influenced the aggregation behavior of A? and could be applied as an A? detection probe for plaque staining in the brains of transgenic AD model mice. The results indicate potential for therapy and diagnosis of AD.
EVALuna2:26279